The roles of vitamin D in the prevention and the therapy of male infertility - O. A. Gromova; I. Yu. Torshin; T. R. Grishina; S. I. Malyavskaya (Izdatelstvo OKI, 2018)
The results of fundamental and clinical studies show the importance of providing males with vitamin D in order to (1) assist the formation of the testicles, (2) maintain the steroid-synthesizing and other functions of the testicles, (3) maintain the functioning of the spermatozoa and, in general, maintain the male fertility.